Conceptual Model of the Supply Chain Control Tower Using Technologies of Blockchain, Agile-Logistic Model and the Concept of Lean-Logistic at Industrial Enterprises - M. A. Ushakov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
In conditions of global economic crisis and restrictions on international trade more and more enterprises in different countries face problems in the field of logistics and restrictions on product import. The current situation makes it necessary to elaborate and use new methods and models of digital production cooperation, which could allow enterprises to exchange needed resources, data, information and knowledge in order to increase efficiency of logistics and production, competitiveness and to cut costs. Besides, lately we can observe a serious breakthrough in the field of digital technologies in all industries, that can be used both in logistics and production and in the future it could provide opportunities for enterprises to work out new models for raising efficiency and quality of products. Based on the mentioned-above facts it is possible to say that the research dealing with the development of methods and models of digital product cooperation in conditions of limited functioning of logistic systems and product import forms an acute and important aspect for developing production spheres both in Russia and other countries. The research findings could be useful for enterprises that face problems in logistics and product import.